2020
DOI: 10.1016/j.jbusvent.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

How to circumvent adversity? Refugee-entrepreneurs' resilience in the face of substantial and persistent adversity

Abstract: People face adverse events in a variety of forms. Some individuals are resilient to adverse events in that they are able to maintain positive functioning while others experience considerable disruption. In explaining heterogeneity in resilience, research has emphasized people's resource endowments and pre-adversity organizing prior to the adverse events as well as people's cognitive and behavioral responses to such events. Therefore, for most resilience studies, adversity is an event. Although it is critically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
131
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(150 citation statements)
references
References 127 publications
(155 reference statements)
2
131
1
Order By: Relevance
“…Several studies have revealed that refugees have a substantial propensity and desire for entrepreneurship (Alexandre et al 2019;Mawson and Kasem 2019;Obschonka et al 2018). Despite traumatic experiences in their home countries and adverse situations in new circumstances, in which refugees need to reconstruct their lives while overcoming various institutional barriers, refugees can demonstrate resilience through entrepreneurial activities (Dionigi 2016;Pieloch et al 2016;Shepherd et al 2020). In their entrepreneurial activities, refugees contribute to their host societies by offering not only economic but also various types of socio-political values.…”
Section: Refugee Entrepreneurshipmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have revealed that refugees have a substantial propensity and desire for entrepreneurship (Alexandre et al 2019;Mawson and Kasem 2019;Obschonka et al 2018). Despite traumatic experiences in their home countries and adverse situations in new circumstances, in which refugees need to reconstruct their lives while overcoming various institutional barriers, refugees can demonstrate resilience through entrepreneurial activities (Dionigi 2016;Pieloch et al 2016;Shepherd et al 2020). In their entrepreneurial activities, refugees contribute to their host societies by offering not only economic but also various types of socio-political values.…”
Section: Refugee Entrepreneurshipmentioning
confidence: 99%
“…Nevertheless, time does not necessarily solve all the issues caused by forcible displacement. Long-standing conflicts have caused several refugee populations, such as Palestinian and Tibetan refugees, to remain disconnected from their homelands over generations (Nayak et al 2019;Shepherd et al 2020;UNHCR 2016).…”
Section: Refugee Entrepreneurshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, diaspora entrepreneurship also focusses on the role of the home country but emphasizes the diasporic nature of entrepreneurs with migration backgrounds, such as homeland orientation and boundary-maintenance (Newland & Tanaka, 2010; Nkongolo-Bakenda & Chrysostome, 2013; Riddle & Brinkerhoff, 2011). Recently, scholars have initiated discussions on refugee entrepreneurship to explore forcibly displaced people as special entrepreneurial agents (Bizri, 2017; Harima & Freudenberg, 2019; Heilbrunn, Freiling, & Harima, 2019; Shepherd, Saade, & Wincent, 2019).…”
Section: Emergence Of Transnational Entrepreneurship As a Research Fieldmentioning
confidence: 99%